2013
DOI: 10.1038/modpathol.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

RASSF2 hypermethylation is present and related to shorter survival in squamous cervical cancer

Abstract: Ras association (RalGDS/AF-6) domain family member 2 (RASSF2) is a gene involved in the progression of several human cancers, including breast, colorectal and lung cancer. The aims of this study were to determine the hypermethylation of the gene in squamous cervical cancer and precursor lesions, along with that of RASSF1 and the recently described EPB41L3, and to analyze the potential prognostic role of these genes. Methylation-specific PCR and bisulfite sequencing were used to analyze the methylation status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
7
39
0
Order By: Relevance
“…RASSF1A (RAS‐association domain family 1) is a potential effector of the Ras oncoprotein, which is involved in the cell cytoarchitecture, apoptosis and cell cycle pathways . RASSF2A is one of the three isoforms encoded by the RASSF2 gene, which participates in Ras signalling and is inactivated by hypermethylation in breast, lung cancer, and, as recently described by our group, squamous cervical carcinoma . The thrombospondin‐1 gene ( TSP1 ) encodes an angiogenesis inhibitor, and its silencing is associated with neovascularization in cancer .…”
Section: Introductionmentioning
confidence: 99%
“…RASSF1A (RAS‐association domain family 1) is a potential effector of the Ras oncoprotein, which is involved in the cell cytoarchitecture, apoptosis and cell cycle pathways . RASSF2A is one of the three isoforms encoded by the RASSF2 gene, which participates in Ras signalling and is inactivated by hypermethylation in breast, lung cancer, and, as recently described by our group, squamous cervical carcinoma . The thrombospondin‐1 gene ( TSP1 ) encodes an angiogenesis inhibitor, and its silencing is associated with neovascularization in cancer .…”
Section: Introductionmentioning
confidence: 99%
“…RASSF2 methylation was also detected in colorectal cancer (CRC), gastric cancer and oral squamous cell carcinoma (please see Table 2 for the complete list and references). In squamous cervical cancer RASSF2 hypermethylation was associated with shorter survival time [146]. Interestingly, in CRC patients the histone modification epigenetic mechanism was probably also involved in silencing of RASSF2, because treating cells with a histone deacetylase inhibitor augmented RASSF2 expression [58].…”
Section: Thementioning
confidence: 99%
“…100 In cervical cancer, methylation of RASSF2 was associated with increased tumor vascular invasion and shorter survival time, independent of tumor stage. 100 Such differences in methylation provide biological insight into the mechanisms of carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…For example, differential methylation patterns have been reported in the progression of several malignancies, including prostate 93,94 bladder, 95,96 renal cell, 47 esophageal, 97 HPV-positive and HPV-negative head and neck, 98,99 and cervical cancers. 100,101 In general, these papers reported that increased DNA methylation within CpG islands was associated with increasing tumor aggressiveness 94,101 and some epigenetic events appear to be early markers of progression. 100 In cervical cancer, methylation of RASSF2 was associated with increased tumor vascular invasion and shorter survival time, independent of tumor stage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation